2019
DOI: 10.3390/ani9080493
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Chitooligosaccharide Inclusion as an Alternative to Antibiotics Improves Intestinal Morphology, Barrier Function, Antioxidant Capacity, and Immunity of Broilers at Early Age

Abstract: This study aimed to investigate the effects of chitooligosaccharide (COS) inclusion as an alternative to antibiotics on growth performance, intestinal morphology, barrier function, antioxidant capacity, and immunity in broilers. In total, 144 one-day-old Arbor Acres broiler chicks were randomly assigned into 3 groups and fed a basal diet free from antibiotics (control group) or the same basal diet further supplemented with either chlortetracycline (antibiotic group) or COS, for 21 days. Compared with the contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 53 publications
7
51
0
Order By: Relevance
“…(2009) reported dietary COS supplementation improved BW gain of broilers. Li et al. (2019) reported dietary COS supplementation increased G:F, accompanied with increasing intestinal barrier function, antioxidant capacity and immunity.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…(2009) reported dietary COS supplementation improved BW gain of broilers. Li et al. (2019) reported dietary COS supplementation increased G:F, accompanied with increasing intestinal barrier function, antioxidant capacity and immunity.…”
Section: Discussionmentioning
confidence: 90%
“…Similarly, in this study, we observed that heat stress increased muscle MDA content and decreased SOD and GSH-Px activity, which indicated a decreased muscle antioxidant capacity, alone with increased lipid peroxidation. Li et al. (2019) reported that dietary COS supplementation increased SOD activity in the duodenum and decreased MDA content in the jejunum of broilers.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Chemical modification of COS can improve its solubility, enhance its biological effects and hold a lower toxicity [15]. COS was widely used in the fields of medicine, pharmacy, and animal husbandry [14,16]. [17].…”
Section: Introductionmentioning
confidence: 99%